Uji Aktivitas Antioksidan Fraksi Ekstrak Kulit Bawang Putih (Allium Sativum L.) dengan Metode FRAP (Ferri Reducing Antioxid Power) - Pratiwi, Rizky Indah; Kalsum, Ummu; Suleman, Abdul Wahid (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Garlic is used by some people to treat itching on the skin which is often known as tinea versicolor. These materials are used by rubbing the itchy skin area. Garlic produces waste in the form of skin, garlic bulb skin contains flavonoids, phenols, alkaloids, tannins and saponins, which have antioxidant activity. This study aims to determine the antioxidant activity of the garlic skin extract fraction (Allium Sativum L.) using the FRAP (Ferric Reducing Antioxidant Power) method and to determine the IC50 value of the garlic skin extract fraction using the FRAP method. The type of research used was experimentation with garlic skin samples extracted using the maceration method with 70% ethanol solvent, then fractions were carried out with polar (ethanol:water) and non-polar (n-hexane) solvents. Antioxidant activity testing using uv-vis spectrophotometry. Based on the results of the descriptive analysis, it showed that the garlic extract and skin fraction samples had antioxidant activity. The results obtained were the ethanol:water fraction was 1.52 ppm and the n-hexane fraction was 2.75. conclution is the polar fraction (ethanol:water) and the non-polar fraction (n-hexane) have strong antioxidant activity.